Desenvolvimento financeiro, desigualdade regional e crescimento: uma aplicação para os estados brasileiros - Melo Neto, Joaquim Lucas de (2023)
The central proposal in this work is to investigate the dynamic relationships between economic growth, financial inequality and income inequality. For this, we propose the construction of a financial development index for the Brazilian states calculated via principal component analysis. In order to reach the proposed objective, the investigation of the influence of one variable on the other, a model of Autoregressive Panel Vectors – PVAR, suggested according to Love e Zicchino (2006), is used. In order to try to investigate and give more subsidies to the results found in the relationship between the variables, a theoretical model was discussed that associates growth, financial development and inequality along the lines of Acemoglu (2008). As a result, based on the theoretical model and the empirical evidence found, the endogenous variable financial development causes regional income inequality and vice versa, which reinforces the hypothesis of intense endogeneity between the variables.